1999
DOI: 10.1046/j.1471-4159.1999.0721890.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtype‐Specific Enhancement of NMDA Receptor Currents by Mutant Huntingtin

Abstract: Evidence suggests that NMDA receptor-mediated neurotoxicity plays a role in the selective neurodegeneration underlying Huntington's disease (HD). The gene mutation that causes HD encodes an expanded polyglutamine tract of >35 in huntingtin, a protein of unknown function. Both huntingtin and NMDA receptors interact with cytoskeletal proteins, and, for NMDA receptors, such interactions regulate surface expression and channel activity. To determine whether mutant huntingtin alters NMDA receptor expression or func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(103 citation statements)
references
References 70 publications
3
98
1
1
Order By: Relevance
“…3C), suggesting that activation of both mGluR1/5 and NMDAR is necessary for dopamine/ glutamate-induced apoptosis of YAC128 MSNs in our in vitro HD model. Htt exp specifically facilitates activity of the NR2B subtype of NMDA receptors (Chen et al, 1999;Sun et al, 2001;Zeron et al, 2002Zeron et al, , 2004Song et al, 2003) and InsP 3 R1 (Tang et al, 2003b). The involvements of NR2B subtype of NMDAR and InsP 3 R were also confirmed by specific blocker of NR2B (ifenprodil) and membrane-permeable InsP 3 R blockers (2-APB and enoxaparin) (Fig.…”
Section: Pharmacology Of Dopamine/glutamate-induced Apoptosis Of Hd Msnsmentioning
confidence: 65%
See 2 more Smart Citations
“…3C), suggesting that activation of both mGluR1/5 and NMDAR is necessary for dopamine/ glutamate-induced apoptosis of YAC128 MSNs in our in vitro HD model. Htt exp specifically facilitates activity of the NR2B subtype of NMDA receptors (Chen et al, 1999;Sun et al, 2001;Zeron et al, 2002Zeron et al, , 2004Song et al, 2003) and InsP 3 R1 (Tang et al, 2003b). The involvements of NR2B subtype of NMDAR and InsP 3 R were also confirmed by specific blocker of NR2B (ifenprodil) and membrane-permeable InsP 3 R blockers (2-APB and enoxaparin) (Fig.…”
Section: Pharmacology Of Dopamine/glutamate-induced Apoptosis Of Hd Msnsmentioning
confidence: 65%
“…1). However, in HD MSNs, mutant Htt exp further potentiates the activity of NR2B NMDAR (Chen et al, 1999;Sun et al, 2001;Zeron et al, 2002Zeron et al, , 2004Song et al, 2003) and InsP 3 R1 (Tang et al, 2003b). Thus, convergence of dopamine and glutamate signaling pathways promotes cytosolic and mitochondrial Ca 2ϩ overload and apoptosis of HD MSNs (Fig.…”
Section: Dopaminergic Signaling and Neurodegeneration Of Hd Msnsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was confirmed that NR2B subtype NMDA receptors activation triggers the selective degeneration of the medium spinal striatal neurons in HD [204]. Mutant huntingtin may increase the number of functional NR1/NR2B-type receptors at the cell surface [205]. Moreover, the expression of polyglutamine-expanded huntingtin results in NMDA receptors sensitization and promotes neuronal apoptosis triggered by glutamate [206].…”
Section: Huntington's Diseasementioning
confidence: 87%
“…[71][72][73][74] Örneğin, aynı glutamat uyarımının uygulanması ve aynı reseptör yoğunluğunda, NR1/NR2A NR1/NR2B'den daha geniş akım amplitüdü gösterir ve daha hızlı de-aktive olur; ancak sonuçta her ikisi de hücre için eşit akım alışı gösterir. 75 Beyinde, gelişim sırasında NR1'ın sekiz farklı kesim çeşidinden (NR1A-H) en az bir tanesi tüm nöronlarda ifade edilirken, NR2 alt üniteleri daha farklı bir dağılım göstermektedir. 76 Prenatal dö-nemde NR2B ve NR2D mRNA'ları baskın durumdayken, NR2A ve NR2C mRNA'ları ancak doğuma yaklaşıldığı dönemde tespit edilebilmiştir.…”
Section: N-meti̇l-d-aspartat Reseptörleri̇unclassified